2016
DOI: 10.1002/jaba.336
|View full text |Cite
|
Sign up to set email alerts
|

The use of picture prompts and prompt delay to teach receptive labeling

Abstract: The current study extended research on picture prompts by using them with a progressive prompt delay to teach receptive labeling of pictures to 2 teenagers with autism. The procedure differed from prior research because the auditory stimulus was not presented or was presented only once during the picture-prompt condition. The results indicated that the combination of picture prompts and prompt delay was effective, although 1 participant required a procedural modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Although simultaneous MTS is widely used when teaching auditory–visual conditional (i.e., listener behavior) relations to children with autism (Bao et al, 2017; Dixon et al, 2017; Kobari‐Wright & Miguel, 2014; McLay et al, 2013; Vedora & Barry, 2016), several prerequisite skills may be at play (Green, 2001; Green & Saunders, 1998). For instance, the participant must differentially respond to a) comparisons that are discriminative (S D ) and nondiscriminative (S‐delta) for reinforcement within a trial (i.e., simple simultaneous discrimination) and, b) each sample across trials (i.e., simple successive discriminations).…”
mentioning
confidence: 99%
“…Although simultaneous MTS is widely used when teaching auditory–visual conditional (i.e., listener behavior) relations to children with autism (Bao et al, 2017; Dixon et al, 2017; Kobari‐Wright & Miguel, 2014; McLay et al, 2013; Vedora & Barry, 2016), several prerequisite skills may be at play (Green, 2001; Green & Saunders, 1998). For instance, the participant must differentially respond to a) comparisons that are discriminative (S D ) and nondiscriminative (S‐delta) for reinforcement within a trial (i.e., simple simultaneous discrimination) and, b) each sample across trials (i.e., simple successive discriminations).…”
mentioning
confidence: 99%
“…Although the differential effects were not replicated in Roger's second comparison, it is possible that this finding has implications for clinicians. Roger was exposed to the DOR during training on three sets of stimuli in a prior study (Vedora & Barry, 2016) and in the first comparison of the current study; thus, it may have been the repeated exposure to the DOR that enhanced control by the sample stimuli in the no-DOR condition of the second comparison. Additional research is needed to determine if repeated exposure to the DOR improves performance in the absence of the DOR during receptive label training.…”
Section: Resultsmentioning
confidence: 95%
“…Roger communicated with an augmentative communication device and manded for several preferred items with vocal approximations. Roger participated in a previous study (Vedora & Barry, 2016) in which picture prompts were used to teach receptive labeling. Dillon was a 21-year-old male diagnosed with Down syndrome.…”
Section: Methods Participants Setting and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, we used a progressively delayed prompting procedure to transfer stimulus control from the controlling prompt to each sample stimulus because it often produces relatively rapid acquisition with few errors and relatively low levels of problem behavior (Green, 2001;Grow & LeBlanc, 2013;Sidman & Stoddard, 1967;Touchette, 1971;Walker, 2008;Weeks & Gaylord-Ross, 1981). Fourth, we selected an identity-match prompt (i.e., a picture prompt that is identical to the correct comparison stimulus) as the controlling prompt, because it ensures that the individual discriminates the correct comparison stimulus from the other comparison stimuli, and research has shown it to be more effective than a point prompt (Carp et al, 2012;Fisher et al, 2007;Jones & Zarcone, 2014;Vedora & Barry, 2016). Fifth, we included an error-correction procedure that involved repeating trials on which the participant emitted an error until the participant emitted an independent correct response for that trial (e.g., Schumaker & Sherman, 1970).…”
mentioning
confidence: 99%